2017
DOI: 10.7717/peerj.2912
|View full text |Cite
|
Sign up to set email alerts
|

­Genomic data mining of the marine actinobacteriaStreptomycessp. H-KF8 unveils insights into multi-stress related genes and metabolic pathways involved in antimicrobial synthesis

Abstract: Streptomyces sp. H-KF8 is an actinobacterial strain isolated from marine sediments of a Chilean Patagonian fjord. Morphological characterization together with antibacterial activity was assessed in various culture media, revealing a carbon-source dependent activity mainly against Gram-positive bacteria (S. aureus and L. monocytogenes). Genome mining of this antibacterial-producing bacterium revealed the presence of 26 biosynthetic gene clusters (BGCs) for secondary metabolites, where among them, 81% have low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 157 publications
1
34
1
2
Order By: Relevance
“…Enriched Bacillus could therefore play a direct role of reducing V(V) in our soil-inoculated systems. Other enriched species observed in our study have previously been reported capable of tolerating heavy metals, such as the actinobacterial strain Streptomyces in marine sediments which tolerates Ni (Undabarrena et al, 2017), Lysobacter which has genes resistant to Co (Puopolo et al, 2016), Microvirga from the arid Taklamakan desert which strongly resists Pb through intracellular precipitations (Luo et al, 2014), and Ramlibacter from chromite ore processing residue-contaminated soils which is resistant to Cr (Min et al, 2017). These metal-tolerant species accumulated abundantly after long-term incubation, and were potentially tolerant to vanadium since vanadium is less toxic than the afore-mentioned metals.…”
Section: Evaluation Of Microbial Remediationsupporting
confidence: 61%
“…Enriched Bacillus could therefore play a direct role of reducing V(V) in our soil-inoculated systems. Other enriched species observed in our study have previously been reported capable of tolerating heavy metals, such as the actinobacterial strain Streptomyces in marine sediments which tolerates Ni (Undabarrena et al, 2017), Lysobacter which has genes resistant to Co (Puopolo et al, 2016), Microvirga from the arid Taklamakan desert which strongly resists Pb through intracellular precipitations (Luo et al, 2014), and Ramlibacter from chromite ore processing residue-contaminated soils which is resistant to Cr (Min et al, 2017). These metal-tolerant species accumulated abundantly after long-term incubation, and were potentially tolerant to vanadium since vanadium is less toxic than the afore-mentioned metals.…”
Section: Evaluation Of Microbial Remediationsupporting
confidence: 61%
“…The synthesis of antimicrobial compounds including polyketide and peptide compounds involves the biosynthetic gene clusters of NRPS and PKS-I, or even the combination of both (Undabarrena et al, 2017). Therefore, an attempt was made to check the presence of these biosynthetic systems in the gDNA of eight strains through PCR specific primers.…”
Section: Resultsmentioning
confidence: 99%
“…The phylum Actinobacteria represents the most prominent group of microorganisms for the production of bioactive compounds [ 5 , 6 , 7 ], contributing to nearly 40% of the bioactive secondary metabolite production, and nearly 80% of which are produced by the genus Streptomyces [ 8 ]. The capability of actinobacterial strains to produce bioactive secondary metabolites relies on their genomic potential, which typically contain a large number of biosynthetic gene clusters, including genes encoding for polyketide synthases (PKS) and non-ribosomal peptide synthetases (NRPS) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%